Analisis Prinsip Kesantunan Berbahasa Netizen di Kolom Komentar Akun Instagram Prabowo Subianto - Desty Endrawati Subroto; Andrean Andrean; Vira Dwi Amalia; Ayu Nurlaela (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study examines the use of politeness principles in netizens’ comments on the Instagram account of Prabowo Subianto. The focus of the research is on utterances that reflect the six maxims of politeness proposed by Leech, namely the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. This research employed a qualitative method with a content analysis approach. The data were collected through digital documentation, listening, and note-taking techniques from netizens’ comments on Prabowo Subianto’s Instagram post dated April 13, 2026. The findings show that five politeness maxims were identified in the data, namely the tact maxim with 78 utterances, the approbation maxim with 145 utterances, the modesty maxim with 4 utterances, the agreement maxim with 190 utterances, and the sympathy maxim with 33 utterances. Meanwhile, the generosity maxim was not found in the data. These findings indicate that the comments on the post generally express polite, appreciative, and supportive attitudes toward Prabowo Subianto.